Situation Report: Hungary, 17 April 1969 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. A Change in the Profit-Sharing System? Developments in the Hungarian Press Kadar on Czechoslovakia Hungarian-Czechoslovak Relations Puja in East Berlin Poetry Day Celebrated Again